2013
DOI: 10.1111/cdev.12113
|View full text |Cite
|
Sign up to set email alerts
|

Disorganized Behavior in Adolescent–Parent Interaction: Relations to Attachment State of Mind, Partner Abuse, and Psychopathology

Abstract: Disoriented, punitive, and caregiving/role-reversed attachment behaviors are associated with psychopathology in childhood but have not been assessed in adolescence. One hundred twenty low-income late adolescents (aged 18 – 23) and parents were assessed in a conflict-resolution paradigm. Their interactions were coded with the Goal-Corrected Partnership in Adolescence Coding Scales. Confirmatory factor analysis demonstrated that the three disorganized constructs (punitive, care-giving, and disoriented interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 78 publications
7
98
0
4
Order By: Relevance
“…This was true for both parents in the specific stress dimension of perceived quality of parent-child interaction. These results support the notion of unresolved attachment as a specific risk factor in the caregiving context when compared with the insecure attachment category (Barone et al, 2014;Obsuth, Hennighausen, Brumariu, & Lyons-Ruth, 2014;Solomon & George, 2011). The results that were obtained are only partially consistent with a previous study involving biological mothers, in which observed (but not self-reported, as in the present study) levels of stress were higher for mothers classified as unresolved (Busch et al, 2008).…”
Section: Hypothesessupporting
confidence: 78%
“…This was true for both parents in the specific stress dimension of perceived quality of parent-child interaction. These results support the notion of unresolved attachment as a specific risk factor in the caregiving context when compared with the insecure attachment category (Barone et al, 2014;Obsuth, Hennighausen, Brumariu, & Lyons-Ruth, 2014;Solomon & George, 2011). The results that were obtained are only partially consistent with a previous study involving biological mothers, in which observed (but not self-reported, as in the present study) levels of stress were higher for mothers classified as unresolved (Busch et al, 2008).…”
Section: Hypothesessupporting
confidence: 78%
“…To fill this gap in the assessment of disorganization in adolescence, Obsuth, Hennighausen, Brumariu, and Lyons-Ruth (2014) recently developed and validated the Goal-Corrected Partnership in Adolescence Coding System (GPACS) to assess both the parent's and the adolescent's disorganized or controlling behavior during a videotaped discussion of a topic of conflict. In the current work, the relations between these disorganized or controlling interactions and borderline symptoms or suicidality were examined in a low-income community sample of 120 young adults.…”
Section: Disorganized and Controlling Behaviors In Infancy And Childhoodmentioning
confidence: 99%
“…Young adult-parent interaction was assessed using the GPACS (Obsuth et al, 2014) applied to a videotaped interaction in which parent and young adult discussed a topic of conflict between them. Parents and young adults separately completed an Issues Checklist on which each person rated sources of disagreement in their relationship.…”
Section: Assessment Of Borderline Symptomatology Suicidality and Dementioning
confidence: 99%
See 1 more Smart Citation
“…Increases in security of attachment have been reported as evidence of the efficacy of the treatment. However, insecure but ordered attachment has not been associated with real psychopathology, whereas disorganized/disordered attachment behavior has been shown to play a role in the development of pathology, as discussed by Obsuth, Hennighausen, Brumariu, and Lyons-Ruth (2014). Ziv (2005) suggested that a good immediate assessment of treatment efficacy may be the examination of reductions in disorganized classifications.…”
Section: Plausibility Theoretical Background and Generalizability Omentioning
confidence: 99%